Identification of Malassezia sp. as a Cause of Dandruff Among Students at Muhammadiyah Polytechnic Makassar - Annisa, Riska; Rasyid, Nur Qadri; Basarang, Mujahidah; Faisal, Restu Andini (Mukhtabar Journal of Medical Laboratory Technology, 2024)
Background & Objective: Dandruff is a scalp condition attributed to the fungus Malassezia sp. It manifests as fine to coarse scales that are grayish or white, resulting from the shedding of the stratum corneum layer on the scalp. Factors contributing to the onset of dandruff include the proliferation of Malassezia fungi, sebaceous gland activity, and individual predisposition. This study aimed to identify Malassezia sp. responsible for dandruff among female students at the Muhammadiyah Polytechnic of Makassar. Method: The research employed a laboratory observational design utilizing a purposive sampling technique. Dandruff samples were collected from 10 female students and cultured on SDA (Sabouraud Dextrose Agar) media, followed by microscopic examination of the resulting colonies. Result: The findings revealed that none of the 10 dandruff samples contained Malassezia sp.; instead, contamination by Aspergillus fumigatus was observed. Conclusion: Therefore, it can be concluded that Malassezia sp. was not identified as a causative agent of dandruff in female students at the Muhammadiyah Polytechnic of Makassar